Heteroaryl-Ethylenes as New Effective Agents for High Priority Gram-Positive and Gram-Negative Bacterial Clinical Isolates - Dalida Angela Bivona; Alessia Mirabile; Carmelo Bonomo; Paolo Giuseppe Bonacci; Stefano Stracquadanio; Andrea Marino; Floriana Campanile; Carmela Bonaccorso; Cosimo Gianluca Fortuna; Stefania Stefani; Nicolò Musso; Dafne Bongiorno (Antibiotics, 2022)
The World Health Organization has identified antimicrobial resistance as a public health emergency and developed a global priority pathogens list of antibiotic-resistant bacteria that can be summarized in the acronym ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacterales species), reminding us of their ability to escape the effect of antibacterial drugs. We previously tested new heteroaryl-ethylene compounds in order to define their spectrum of activity and antibacterial capability. Now, we focus our attention on PB4, a compound with promising MIC and MBC values in all conditions tested. In the present study, we evaluate the activity of PB4 on selected samples of ESKAPE isolates from nosocomial infections: 14 S. aureus, 6 E. faecalis, 7 E. faecium, 12 E. coli and 14 A. baumannii. Furthermore, an ATCC control strain was selected for all species tested. The MIC tests were performed according to the standard method. The PB4 MIC values were within very low ranges regardless of bacterial species and resistance profiles: from 0.12 to 2 mg/L for S. aureus, E. faecalis, E. faecium and A. baumannii. For E. coli, the MIC values obtained were slightly higher (4–64 mg/L) but still promising. The PB4 heteroaryl-ethylenic compound was able to counteract the bacterial growth of both high-priority Gram-positive and Gram-negative clinical strains. Our study contributes to the search for new molecules that can fight bacterial infections, in particular those caused by MDR bacteria in hospitals. In the future, it would be interesting to evaluate the activity of PB4 in animal models to test for its toxicity.